‘A Prison Is a Prison’: perspectives From Incarcerated Men on the Therapeutic and Punitive Aspects of Halden Prison in Norway - Abdel-Salam, Sami (The British journal of criminology, 2023)
Halden prison in Norway was architecturally designed to create a humane space conducive to mental wellbeing and motivation for personal growth. However, little is known about how those imprisoned perceive these design choices and its impact on their daily lived experience. The current study uses data from surveys and semi-structured interviews to examine the perceptions of incarcerated men at Halden regarding the prison’s design and its effect on overall impressions of the prison, therapeutic benefits and experiences of punishment. Findings indicate that although incarcerated individuals acknowledge the positive design elements of the prison, they do not perceive a therapeutic or motivational benefit. Furthermore, certain ‘pains’ of imprisonment persist within this environment, and the juxtaposition of therapeutic design elements and security practices may have unintended punitive effects. Results from this study serve as an important counterbalance to overwhelmingly favorable impressions of Halden’s design as mitigating the pains of imprisonment while promoting rehabilitation.